Pressurized Liquid Extraction (PLE) and QuEChERS evaluation for the analysis of antibiotics in agricultural soils - da Silva, Josiel José [UNESP] (2020)
Vinasse, a liquid waste which originates from the production of ethanol fuel from sugarcane, has been widely used as soil amendment in Brazil. An important concern that arises from vinasse reuse is the dissemination of antibiotics to the environment through crop soils. This work evaluated the performance of Pressurized Liquid Extraction (PLE) and QuEChERS (quick, easy, cheap, effective, rugged and safe) to extract several multiple-class antibiotics, such as cephalosporins, fluoroquinolones, ionophores, lincosamides, macrolides, quinolones, streptogramin, sulfonamides, tetracyclines and others, from agricultural soils. The performance of several parameters was evaluated for both PLE and QuEChERS, such as the extraction temperature (for PLE), solvents composition, pH and the addition of EDTA. Both methods were able to extract most target antibiotics. However, QuEChERS showed higher recoveries for macrolides and nitroimidazoles, while PLE was more suitable for fluoroquinolones and ionophores (i.e. monensin). The use of citrate-phosphate buffer at pH 7.0, in combination with methanol for PLE and with acetonitrile for QuEChERS, provided the highest antibiotic recoveries for both methods. The use of EDTA did not increase antibiotic recovery rates for QuEChERS, while the temperature had almost no influence on the extraction efficiency in PLE. • Citrate-phosphate buffer at pH 7.0 provided higher antibiotic recoveries for QuEChERS and PLE. • The combination buffer-methanol provided higher recoveries for PLE. • QuEChERS and PLE methods were able to extract most of the target antibiotics.